Distinct effects of short- and long-term type 1 diabetes to the placental extracellular matrix and fetal development in mice. (May 2017) - Sanches, Juliane C.; Favaro, Rodolfo R.; Barrence, Fernanda C.; Bevilacqua, Estela; Fortes, Zuleica B.; Zorn, Telma M.T.
Abstract: Purpose: We have previously shown that the development of complications in the early pregnant decidua and myometrium in mice correlates with diabetes progression. In the current study, we investigated the influence of diabetes progression on the placental extracellular matrix (ECM) and on fetal development at the end of pregnancy. Methods: Alloxan-induced type 1 diabetic female mice were bred either 30–50 days after diabetes induction (D) or 90-110D. Fetal and placental weights were registered at the 19th day of pregnancy together with analysis of gene expression, deposition and turnover of the placental ECM. Results: The short-term diabetic group (30-50D) showed elevated embryonic losses and underweight fetuses (89%) with normal weight placentas. In contrast, the long-term group (90-110D) had increased malformations/fetal deaths and underweight fetuses (42%) and heavy placentas (50%). Normal-weight fetuses from the long-term group had placentas with either regular weight and fetal/placental weight ratio or increased weight and low fetal/placental weight ratio. Furthermore, the placentas of the short-term group showed alterations in the synthesis and deposition of collagen types I and V and in the activity of MMP2 whereas placentas of the 90-110D group presented alterations in collagen type III and V and MMP9. Conclusions: Diabetes progression promoted distinct outcomes in pregnancy. Modifications of both synthesis and turnover of ECM occurred even before changes of placental weight were detected. Adjustment of fetal/placental weight ratio or placental enlargement restored normal growth in part of the fetuses from the long-term group. Highlights: Diabetes progression in mice leads to distinct placental and fetal outcomes. Synthesis and turnover of placental ECM change during diabetes progression. Changes of the ECM occur before the reshaping of diabetic placental weight. Fetal/placental weight ratio adjustment or placental enlargement rescue fetal growth.